Staged Percutaneous Intervention for Concurrent Chronic Total Occlusions in Patients With ST‐Segment–Elevation Myocardial Infarction: A Systematic Review and Meta‐Analysis. Issue 8 (11 September 0207) - Villablanca, Pedro A.; Olmedo, Wilman; Weinreich, Michael; Gupta, Tanush; Mohananey, Divyanshu; Albuquerque, Felipe N.; Kassas, Ibrahim; Briceño, David; Sanina, Cristina; Brevik, Thomas A.; Ong, Emily; Ramakrishna, Harish; et al.
Abstract : Background: Studies have shown that chronic total occlusion (CTO) in a noninfarct‐related artery in patients with ST‐segment–elevation myocardial infarction is linked to increased mortality. It remains unclear whether staged revascularization of a noninfarct‐related artery CTO in patients with ST‐segment–elevation myocardial infarction translates to improved outcomes. We performed a meta‐analysis to compare outcomes between patients presenting with ST‐segment–elevation myocardial infarction with concurrent CTO who underwent percutaneous coronary intervention of noninfarct‐related artery CTO versus those who did not. Method and Results: We conducted an electronic database search of all published data. The primary end point was major adverse cardiovascular events. Secondary end points were all‐cause mortality, cardiovascular mortality, myocardial infarction, repeat revascularization with either percutaneous coronary intervention or coronary artery bypass grafting, stroke, and heart failure readmission. Odds ratios (ORs) and 95% confidence intervals (CIs) were computed. Random effects model was used and heterogeneity was considered if I 2 >25. Six studies (n=1253 patients) were included in the analysis. There was a significant difference in major adverse cardiovascular events (OR, 0.54; 95% CI, 0.32–0.91), cardiovascular mortality (OR, 0.43; 95% CI, 0.20–0.95), and heart failure readmissions (OR, 0.57; 95% CI, 0.36–0.89), favoring the patients in the CTO percutaneous coronary intervention group. No significant differences were observed between the 2 groups for all‐cause mortality (OR, 0.47; 95% CI, 0.22–1.00), myocardial infarction (OR, 0.78; 95% CI, 0.41–1.46), repeat revascularization (OR, 1.13; 95% CI, 0.56–2.27), and stroke (OR, 0.51; 95% CI, 0.20–1.33). Conclusions: In this meta‐analysis, CTO percutaneous coronary intervention of the noninfarct‐related artery in patients presenting with ST‐segment–elevation myocardial infarction was associated with a significant reduction in major adverse cardiovascular events, cardiovascular mortality, and heart failure readmissions.